2008
DOI: 10.1590/s1516-35982008000800013
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos dos níveis de energia, lisina e metionina + cistina sobre o desempenho e o rendimento de carcaça de frangos de corte

Abstract: RESUMO -Avaliaram-se os efeitos dos níveis de energia, lisina, metionina + cistina na ração sobre o desempenho e os rendimentos de carcaça e cortes de frangos de corte. O delineamento experimental foi o inteiramente ao acaso, em esquema fatorial (3 × 2), composto de seis tratamentos e oito repetições (quatro para machos e quatro para fêmeas).Os tratamentos foram definidos pelos níveis de energia (baixo, médio e alto), lisina e metionina + cistina (padrão ou 10% superiores ao recomendado) e pelo período de cria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
4
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 11 publications
4
4
1
13
Order By: Relevance
“…Concerning the abdominal fat percentage, similar results were found by Duarte et al (2007) and Lima et al (2008), who observed no effect of the energy levels on abdominal fat. However, these findings differ from the results presented by Mendes et al (2004), who found increase in the abdominal fat by evaluating increasing levels of energy.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Concerning the abdominal fat percentage, similar results were found by Duarte et al (2007) and Lima et al (2008), who observed no effect of the energy levels on abdominal fat. However, these findings differ from the results presented by Mendes et al (2004), who found increase in the abdominal fat by evaluating increasing levels of energy.…”
Section: Resultssupporting
confidence: 89%
“…The results found confirm the ones obtained by Braga & Baião (2001) and Mendes et al (2004), who found improved feed conversion in broiler chickens fed a diet with higher energy density, differing, however, from the results obtained by Lima et al (2008), who found no improvement in feed conversion utilizing different energy levels.…”
Section: Resultssupporting
confidence: 88%
“…na produção de frangos de corte apresentarem diferentes velocidade de crescimento e rendimento de carne (Moreira et al, 2004e Santos et al, 2005. As exigências do mercado são crescentes com relação aos produtos avícolas, o qual busca maior rendimento de carcaças, de cortes e de produtos processados para os diferentes genótipos (Lima et al, 2008). http: //dx.doi.org/10.1590/1678-4162-8241 Arq. Bras.…”
unclassified
“…Com o melhoramento genético, vem a necessidade de se fornecer aos animais uma alimentação que maximize o desempenho e a eficiência produtiva, reduzindo a deposição de gordura associada ao balanço dietético e à grande capacidade de consumo dos genótipos comerciais atuais (Lima et al, 2008).…”
unclassified
See 1 more Smart Citation